E-Cigarettes in India: An Overview - Karishma Rathore1, Debasruti Naik2 , Stithaprajna Lenka3 , Dharmashree Satyarup4 , Nikita Sahu (Indian Journal of Forensic Medicine & Toxicology, 2020)
Knowing its harmful effects, e-cigarettes are still famous among all the tobacco consumers. E-Cigaretteshowever wanted to capture the market in India also since 2016 but has failed to make its mark because ofthe prompt action by the government as compared to the scenario in the western countries. This article willprovide the knowledge and information regarding E-Cigarettes legalization and utilization in India.